Fleet arrival management system : optimizing and sequencing of Icelandair's arrival times - Perla Ásmundsdóttir 1994- (2019)
At hub airports, multiple flights from the same airline often arrive at the same time. These arriving flights must be separated from one another and sequenced. This is done by air traffic control relatively close to the airport. From the point of view of the airline, how flights are sequenced and when they will arrive is often somewhat unpredictable. The final sequence may be suboptimal, and restrictions imposed to separate flights may cause delays or otherwise unnecessary fuel expenditure. Another issue is that en-route flights are in many cases flying at suboptimal speeds due to the unpredictability of delays during departure. Their planned speed may be too fast, causing needless fuel burn, or too slow, causing issues with passenger connections and aircraft schedules upon arrival. Furthermore, the estimated arrival times of inbound flights are often somewhat inaccurate, making the planning of ground operations on arrival more difficult. Inaccurately estimated arrival times may also complicate the job of air traffic control. This study sought to alleviate these problems by developing a process of a Fleet Arrival Management System, a system that optimizes speeds of airborne flights and sequences their arrival times. Application of the developed procedures promotes the eventual separation of flights upon arrival, resulting in improved sequencing and flight profiles. Speeds are optimized to improve fuel economy or to prevent passengers from missing connections or upsetting aircraft schedules. Icelandair is an ideal choice for implementing a Fleet Arrival Management System due to the nature of its route network and hub at Keflavík International Airport. In this thesis, the main components of a Fleet Arrival Management System were proposed and developed, and potential cost savings to Icelandair’s operations were identified and quantified. Trials were conducted in co-operation with Icelandair to prove the concept of this thesis. Although limited in number, they were successful in demonstrating the potential of fully ...